Development of Algorithm of Surgical Treatment Choice in Patients with Cataract and Asteroid Hyalosis - S. A. Korotkikh; A. G. Grinev; M. B. Sviridova; A. M. Danilov (Oftalʹmologiâ)
The method of phacovitrectomy can be used for surgical treatment of patients with cataract and asteroid hyalosis. However, there is still a topical question in the choice of surgical treatment taking into account the completeness of the posterior hyaloid membrane (PHM) detachment.Patients and methods: the study involved 24 patients (24 eyes) with cataract and asteroid hyalosis. The average age of patients was 72.9 years, out of the total number of men — 11, women — 13. Pre-and postoperative diagnosis of all patients included standard methods of investigation, as well as optical coherence tomography performed on the Cirrus HD-OCT 400, Carl Zeiss, Germany. Pre-and postoperative subjective satisfaction was assessed using a validated visual Function Qusetionnaire 14 ophthalmological questionnaire. Patients were divided into 3 groups. In the first group of patients, cataract phacoemulsification with posterior chamber lens implantation and total three-port vitrectomy through a flat part of the ciliary body were performed. In the second patients’ group, cataract phacoemulsification with posterior chamber lens implantation and subtotal vitrectomy through posterior capsulorexis were performed. In the third group of patients, cataract phacoemulsification with posterior chamber lens implantation was performed. All operations were performed with the help of ophthalmic systems Infinity Vision System (Alcon, USA) and Constellation Vision System (Alcon, USA).Results: in the first day after the operation, all patients noted improvement in visual acuity and quality of life, but more significant improvement was noted in patients of the first and second groups.Conclusion: analysis of the results of surgical treatment, questionnaire survey, preoperative diagnosis allowed to develop an algorithm for choosing the method of surgical treatment in patients with cataract and asteroid hyalosis, taking into account the state of PHM.